SIKAP KONSUMEN TERHADAP ATRIBUT BERAS ORGANIK - Rifandy Adrianto (Ma Chung Press, 2018)
Rice is a very important commodity because more than 90% of Indonesians consume rice. Organic rice is rice produced through organic production processes based on certain standards and has been certified by an independent body. The study aims to analyze consumer attitudes toward organic rice product. This study takes 200 people as respondents and uses Fishbein's attitude model to examine the attitude toward the organic rice product relating to the characteristics or attributes of the product. Fishbein's attitude model can explain two types of attitudes based on the object of attitude, namely attitudes toward objects and attitudes toward behavior. Attitude is formed by the belief that an object has some desired attributes and an evaluation of attributes possessed by an object. The results of study concluded that consumer attitudes toward organic rice are positive. Consumer attitude based on the value and based on the mean show positive result which means the attitude of consumers to organic rice is positive.